Current Situation of Malaria and Resistance of Main Vectors to WHO Recommended Insecticides in an Endemic Area, Southeastern Iran. Issue 2 (27th December 2021) - Saberi, Nasrollah; Raeisi, Ahmad; Gorouhi, Mohammad Amin; Vatandoost, Hassan; Mashayekhi, Minoo; Nikpour, Fatemeh; Bozorg Omid, Faramarz; Rahimi Foroushani, Abbas; Hanafi-Bojd, Ahmad Ali
Abstract: Although malaria is endemic in some areas of southeastern Iran, following the successful national malaria elimination plan, the local transmission area has been shrunk. The main cases in Iran are due to Plasmodium vivax followed by P. falciparum . This study was aimed to determine the current situation of malaria in Kerman Province of Iran and evaluate the insecticide resistance of main vectors. The field study was conducted in 2019. Data of new malaria cases were obtained from the health centers for the period of 2009–2018. Susceptibility status of Anopheles stephensi and An. dthali was evaluated against dichlorodiphenyltrichloroethane, Dieldrin, Malathion, Bendiocarb, Deltamethrin, and Temephos at the diagnostic dose. A total of 522 malaria cases were recorded and divided into indigenous (33.14%) and imported (66.86%) categories. The highest incidence of the disease was reported from the southern areas of the province, where all indigenous cases occurred. Adults of An. stephensi were resistant to dichlorodiphenyltrichloroethane while its resistance to be confirmed to dieldrin, bendiocarb and deltamethrin. As An. dthali had less than 98% mortality against bendiocarb, the resistance status should be confirmed with more tests. Our findings showed both species had less than 98% mortality against bendiocarb and deltamethrin insecticides which are used in malaria vector control program in Iran. Due to the susceptibility of these vectors to temephos, larviciding can be advised for vector control in this area.